Effect of Chemical Treatment on Silicon Manganese : Its Morphological, Elemental and Spectral Properties and Its Usage in Concrete - Chin, Mei Yun; Muhammad Khusairy, Bakri; Md Rezaur, Rahman; Kuok, King Kuok; Law, Perry Nyuk Khui; Durul, Huda (Springer Nature, 2022)
The efect of chemical treatment on silicon manganese slag and the efect of curing time on the compressive strength of completely replacement coarse aggregate silicon manganese concrete (SMC) relative to normal weight concrete (NWC) with gravel as coarse aggregate is the subject of this paper. Alkali and acidic base chemicals are used to alter the neat silicon manganese slag during chemical preparation. The mixture pattern proportions for Grade 30 and Grade 50, respectively, were used to create the concrete. Before the compressive strength tests, the samples were cast and cured for 7-, 14-, and 28-days. The properties of the silicon manganese slag and its concrete were studied using a scanning electron microscope (SEM), energy dispersive x-ray spectroscopy (EDS), and Fourier transform infrared spectroscopy (FTIR). The compressive strength of SMC30 and SMC50 obtained were 37.3 MPa and 51.1 MPa, respectively, on the 28-day. The alkaline treatment smoothest the matrix, while the acid treatment roughens the composition of the silicon manganese slag, according to SEM. The functional group demonstrated a major improvement in FTIR, while EDS revealed a high content of both silicon (Si) and manganese (Mn) elements. As a result, it can be observed that the power of SMC increases as the curing time increases for samples with complete replacement of normal aggregates using silicon slag.